Day 3 Wed, October 11, 2017 2017
DOI: 10.2118/187425-ms
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Relative Permeability Hysteresis on Water-Alternating-Gas WAG Injectivity: Modeling and Experimental Study

Abstract: Gas injection is a proven enhanced oil recovery (EOR) process, representing the leading EOR-technique in the United States. In recent years, gas EOR technologies are expanding to more challenging (deeper and tighter) reservoirs. In gas injection, there are two basic techniques – continuous gas flooding and water-alternating-gas (WAG) injection. The WAG injection promises improved sweep efficiency, with water being used for mobility control and stabilizing displacement fronts, but suffers from injectivity loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…(1) Decrease in injection capacity [72,76,77] The hysteresis effect of phase permeability can lead to an increase in injection well pressure, especially during water injection after gas displacement. Once the pressure reaches a certain level, it may result in the inability to inject water and gas.…”
Section: The Impact Of Relative Permeability Hysteresis On Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Decrease in injection capacity [72,76,77] The hysteresis effect of phase permeability can lead to an increase in injection well pressure, especially during water injection after gas displacement. Once the pressure reaches a certain level, it may result in the inability to inject water and gas.…”
Section: The Impact Of Relative Permeability Hysteresis On Recoverymentioning
confidence: 99%
“…At the front edge of the CO 2 slug, gas continues to displace the wetting phase during drainage, while at the rear edge, water displaces gas during imbibition, leading to gas phase fragmentation and subsequent trapping. As the slug migrates upwards, some CO 2 is trapped as residual immobile phase in pore spaces, effectively isolating CO 2 in the rock until the immobile gas dissolves over geological time [11,73,74,76,77,[85][86][87].…”
Section: The Impact Of Relative Permeability Hysteresis On Co 2 Seque...mentioning
confidence: 99%
“…Although conventional two-phase hysteresis models assume the reversibility of permeability during the drainage process following the previous imbibition cycle, this assumption is invalid for three-phase fluid flow because the relative permeability of gas is lower when displacing a water-oil mixture than when displacing oil only [29]. The three-phase hysteresis model proposed by Larsen and Skauge [30] is adopted in the present study and has shown better matching to experimental data than the two-phase model [31,32].…”
Section: The Three-phase Hysteresis Model For Residual Trappingmentioning
confidence: 99%